Dietary Pattern and Their Association With Level of Asthma Control Among Patients With Asthma at Al-Shifa Medical Complex in Gaza Strip, Palestine. (April 2019) - el Bilbeisi, Abdel Hamid Hassan; Albelbeisi, Ali; Hosseini, Saeed; Djafarian, Kurosh
Background: This study was conducted to identify major dietary patterns and their association with level of asthma control among patients with asthma in Gaza Strip, Palestine. Methods: This cross-sectional study was conducted among a representative sample of Palestinian patients with asthma (both sex, aged 19-64 years) receiving care in chest department at Al-Shifa Medical Complex. Asthma control level was obtained using asthma control test. Data regarding other variables were obtained using an interview-based questionnaire and a semi-quantitative food frequency questionnaire. Statistical analysis was performed using SPSS version 20. Results: Two major dietary patterns were identified including (1) Prudent pattern characterized by a high intake of whole grains, beans and legumes, fish and shellfish products, vegetables, tomatoes, fruits, and vegetable oils, and (2) Western pattern characterized by a high intake of refined grains, red meat, poultry, fast foods, eggs, low-fat dairy product, high-fat dairy products, hydrogenated fats, olive, sugar, sweets, desserts, and snacks. After adjustment for confounding variables, patients in the lowest tertile (T1) of Prudent pattern had a lower odds for poorly controlled asthma (odds ratio [OR] = 0.044, 95% confidence interval [CI] = [0.002-1.316], P value < 0.05), whereas patients in the lowest tertile (T1) of Western pattern had a higher odds for poorly controlled asthma (OR = 2.499, 95% CI = [1.288-4.850], P value < 0.05), compared with those in the highest tertile (T3). Conclusion: A Prudent pattern may be associated with a lower prevalence of poorly controlled asthma, whereas a Western pattern may be associated with a higher prevalence of poorly controlled asthma.